Patterns of Transcendence in the Early Buddhist Tradition: The Place of Wilfred Cantwell Smith in the Western Study of the Buddhist Tradition (Al-Qamar, 2023)
This paper[i] examines the ideas of Wilfred Cantwell Smith about the early Buddhist tradition, and his place in the Western studies of Buddhism. It is discussed how the initial efforts of Western scholars paved the way for Buddhist studies to become an academic discipline in European universities. Since the study is about the early Buddhism, the Anglo-German school is focused for their contribution to the study of earlier school known as Theravada. The Theravada tradition strictly rejected the notion of God or divine. Therefore, concepts-such as- Self, Nirvana, and Dharma are of utmost importance in Western interpretive study of early Buddhism. The paper discusses the differences among the Western scholars regarding the meaning of these concepts in order to show Wilfred Cantwell Smith’s contributions in this regard. Smith’s emphasis on the faith of a Buddhist is interconnected with his critique of the notion of ‘religion.’ He is of the view that ‘religion’ as a concept has belittled the importance of faith in transcendence under the impact of modern Western secularism. He significantly emphasizes the notion of Dharma to describe faith in the early Buddhism. Smith considers Dharma as the transcendence with which a faithful Buddhist is involved. This, however, does not preclude Nirvana as an ultimate the transcendence. Hence, if Nirvana is conceptually an unapproachable transcendence that is beyond mundane, Dharma is an achievable transcendence in the mundane realm, according to Smith. Dharma as a transcendent moral ideal, thus, becomes the object of faith in the early Buddhist tradition. In this way, Smith, in addition to his unique analysis, agrees with Western Buddhologists who are not willing to deny divine in the Theravada tradition despite the tradition’s unequivocal rejection of such ideas. [i] The paper is partly based on the PhD dissertation entitled ‘The Notion of Transcendence in the Study of Religion: A Comparative Study between Wilfred Cantwell Smith and Ismail Raji al-Faruqi’ written by the first author of this paper.
Keywords: Theravada; Dharma; Nirvana; Transcendence; Self; Faith; Symbols; Buddhology